Maintenance Analysis of Tension Measurement System on Cutter Machine Using Reliability Centered Maintenance (RCM) - Dwi Nova Catharina Ramadhini Nainggolan; Asep Erik Nugraha; Wahyudin (TALENTA Publisher, 2026)
PT XYZ is a manufacturing company in the paper industry with a continuous production system, making machine reliability a critical factor in maintaining smooth processes and high product quality. A vital system within the Cutter Strachain Henshain Machine (SHM) is the tension measurement system, which regulates paper web tension during the handling process. Field observations at PT XYZ revealed recurring disturbances caused by tension reading failure, which created significant discrepancies between Human Machine Interface (HMI) readouts and actual paper web conditions. While Reliability Centered Maintenance (RCM) is widely studied, its application to vintage, highly sensitive paper-tension control loops operating continuously for over two decades represents a distinct socio-technical operational gap. This study aims to analyze the maintenance strategy of the SHM tension measurement system using the RCM method to address this critical gap. Using a descriptive empirical approach incorporating structured observation, historical maintenance logging, and technical interviews, the system's operational functions, functional failure, and failure modes were systematically mapped. The analytical findings demonstrate that the primary point of failure stems from localized sensor contamination and localized degradation, severely compromising tension reading accuracy. Implementing an RCM-guided maintenance strategy, specifically through scheduled condition-directed maintenance and structured functional testing, is recommended. Quantitative projections indicate that these interventions can reduce total machine downtime by up to 15.4%, optimizing continuous production stability and mitigating cascading cutting defects.